Developing a model for building resilience to climate risks for cultural heritage. Issue 2 (17th August 2015) - O'Brien, Geoff; O'Keefe, Phil; Jayawickrama, Janaka; Jigyasu, Rohit
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to propose a model for developing climate adaptation strategies to reduce climate risk for cultural heritage. Cultural heritage has an important role in human well-being. This paper posits that cultural heritage requires an approach that recognises the uniqueness of cultural heritage. The paper draws from the United Nations International Strategy for Disaster Reduction (UNISDR) Making My City Resilient campaign and the Heart of the City Partnership in Newcastle upon Tyne, UK, and proposes a Cultural Heritage Adaptation Forum. The role of the forum is to develop adaptation strategies in a sustainable development context. This is an original attempt to link cultural heritage to climate risk. Design/methodology/approach – The paper draws from two initiatives and uses good practice established from the disaster management and climate communities and proposes a Cultural Heritage Adaptation Forum that can be used to formulate adaptation interventions for cultural heritage. The approach builds on active participation in a global overview of cultural heritage and climate risk led by UNISDR together with personal experience of implementing such strategies in Newcastle upon Tyne, UK. Findings – The paper finds that a model can be developed that incorporates good practice from the climate and disaster management communities. Practical implications – The paper presents a model that can be used by those stakeholders that have an interest in protecting cultural heritage form climate driven hazards. Social implications – Cultural heritage has a value for all and protecting it from climate driven hazards can impact human well-being Originality/value – The paper brings together concepts from different academic and practitioner communities. The concept outlined in the paper will be of interest to all those interested in protecting cultural heritage for climate driven hazards.